Conversion of Oil Shale To Liquid Hydrocarbons as A New Energy Resources Using Iron (Fe)-Pillared Clay (Kaolinite) Catalyst - Dewanto, Ordas; Ferucha, Istifani; Darsono, Darsono; Rizky, Sri (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
In the context of new energy exploration, oil shale is currently a source of energy that is being developed so that it can be used as an alternative energy in the future. Based on this background, it is important to research the conversion method of oil shale to liquid hydrocarbons. The method used is using clay (kaolinite) catalyst and  iron (Fe)-pillared clay (kaolinite) catalyst. Clay catalyst products are capable of making organic mature faster and even requiring a lower temperature for the changes (through thermal cracking of non-volatile organic material). The addition of Fe metal in the clay catalyst product to oil shale, causing the surface area of the natural clays were significantly increased, then the volume of micro pore were also increased, it causes the organic material to mature faster and the temperature required for the change is less than the shale material without Fe. The catalyst method by the pillarization technique able to increase the surface area and pore volume, thus accelerating the reaction and changing the reaction rate to be greater. It is observed that clay catalyst products can serve as catalysts for accelerating organic maturation reactions. if compared between the clay material  of OD1-Ast1 (50% clay-50% organic), OD1-Ast2 (33% clay-67% organic), and the OD1-Ast3 shale material (67% clay - 33% organic),then OD1-Ast3 has a faster reaction rate. Comparison of clay material is smaller than organic, then the properties of the catalyst product to accelerate the reaction are reduced, such as the OD1-Ast2 shale material has a slow reaction rate compared to the OD1-Ast3 shale material. The addition of Fe metal in the clay catalyst product to the OD1-Ast2 shale material, resulting in OD1-Ast2-Fe shale material (75% OD1-Ast2 and 25% Fe) having a faster reaction rate than before the addition of Fe metal.The design of heavy (%) clay (kaolinite) and Fe pilaration on oil shale were greatly influence the change of TOC values when heated,then affecting maturation and Tmax. The temperature of maturation and Tmax as the main parameters of conversion of oil shale to liquid hydrocarbon. This method supports the development of science and technology in the field of exploitation and processing of natural resources.